Membangkitkan Potensi: Transformasi SDM UMKM Happy Kue Lompong Melalui Pelatihan Inovatif - Handayani, Nilam; Razak, Nirwan (Amsir Management Journal, 2024)
This study analyzes the training and human resource development program in Happy Kue Lompong MSMEs. Using a descriptive qualitative approach, the data was collected through observation and interviews, and then analyzed with the Miles and Huberman model. The results show that the program is implemented according to employees' needs and working conditions, aiming to increase their understanding, motivation, and capacity. The method used is work-in-progress education. The benefits are felt by employees and non-employees alike. Supporting factors include organizational support while inhibiting factors include a lack of post-training attention and employee motivation. The evaluation is carried out informally between the employee and the owner.